3D imaging and quantification of PLL coated fluorescent ZnO NP distribution and ROS accumulation using laser scanning confocal microscopy. Issue 9 (25th June 2022) - Dey, Aishee; Gare, Suman; Swain, Sarpras; Bhattacharya, Proma; Dhyani, Vaibhav; Giri, Lopamudra; Neogi, Sudarsan
Abstract: Investigations on nanomedicine involve conventional two dimensional (2D) imaging techniques for observing the nanoparticle internalization at a single time point where various phases of internalization can be overlooked. In contrast, three dimensional (3D) imaging of fluorescent nanoparticles with anticancer potential can be used for obtaining the time course of cellular retention of particles, and cells can be followed for days. This article demonstrates the application of laser scanning confocal microscopy to quantify poly‐l ‐lysine coated fluorescent ZnO nanoparticle retention and reactive oxygen species (ROS) generation using volumetric imaging. Synthesis of these particles allows monitoring of ROS formation, internalization, and cytotoxicity using the same imaging platform that offers an advantage over measurement using various instruments. PLL‐coated ZnO particles' ability to induce a significant reduction in cell‐viability suggests its potential as a therapeutic agent. The proposed framework opens up a new avenue for investigating mechanistic aspects of ZnO adsorption and the evaluation of therapeutic efficiency.